A Review on Mechanical & Physical Hazards at Domestic Kitchen - Mondal, Jaita (International Journal of Occupational Safety and Health, 2012)
Kitchen is one of the most important aspects in our life. We wait eagerly for the delicious foodstuffs of our kitchenette. However, many simple but repetitive kitchen activities can be a threat to our health. Such as peeling potatoes, chopping, and picking up heavy pots and kettles, overstretching to reach to utensils or ingredients etc. can cause or aggravate pain & discomfort in hand, wrist, elbow, shoulder and neck (Physical hazards). Musculoskeletal problems are not only the one, but various accidents also happen in domestic kitchen (Mechanical Hazards). Traumatic and repetitive injuries related to kitchen tasks include lacerations, cut, slips & falls, tendonitis, carpal tunnel syndrome, thermal strains, burn etc. Those menaces generally occur due to poor ergonomics, as poor work practices, poor quality equipment and poorly maintained equipment. DOI: http://dx.doi.org/10.3126/ijosh.v2i1.5920 International Journal of Occupational Safety and Health, Vol. 2 No. 1 (2012) 7-10